Correlação entre a SvO2 e SjO2 durante a cirurgia cardíaca com circulação extracorpórea em crianças SjO2/SvO2 correlation during pediatric cardiac surgery with cardiopulmonary bypass - Jyrson Guilherme Klamt; Pamela Regina Teixeira Nabarro; Walter Villela de Andrade Vicente; Luis Vicente Garcia; Cesar Augusto Ferreira (Brazilian Journal of Cardiovascular Surgery, 2011)
OBJETIVOS: Analisar a correlação entre a SvO2 (indicador do débito cardíaco) e a SjO2 (indicador da oxigenação cerebral) durante cirurgias cardíacas com circulação extracorpórea (CEC) em crianças. MÉTODOS: Estudo retrospectivo. Dados da SjO2, SvO2 e SaO2, mensurados simultaneamente em momentos críticos da cirurgia cardíaca com CEC, em 12 crianças, foram analisados pelo teste de correlação de Spearman e pela representação gráfica de Bland-Altman. RESULTADOS: Foram encontrados baixa correlação entre a SjO2 e a SvO2 (r²=0,14, P=0,03) e um viés alto (-7,8) na plotagem de Bland-Altman, indicando independência entre as duas variáveis. SjO2 < 50% (indicativo de isquemia-hipoxia cerebral) foi observada em cerca de 50% das medidas após o reaquecimento no final da CEC hipotérmica. CONCLUSÕES: A medida de SvO2 não é preditiva da SjO2 durante a cirurgia cardíaca com CEC em crianças e baixa SjO2 pode deixar de ser detectada medindo-se apenas a SvO2. OBJECTIVES: To compare the SjO2 (cerebral oxygenation indicator) and SvO2 (cardiac output indicator) during pediatric cardiac surgery with cardiopulmonary bypass (CPB). METHODS: Retrospective study. Data of SjO2 and SvO2 measured simultaneously at critical time periods during cardiac surgery with CPB were analyzed by the Spearman correlation test and Bland- Altman plot. RESULTS:Regression analysis of the pooled data showed poor correlation between SjO2 and SvO2 (r²=0.14, P=0.03) and Bland- Altman plot had a high bias (-7.9), indicating independency of the two variables. SjO2<50% (indicative of cerebral ischemia-hypoxia) were observed in 50% of the measurements after rewarming during hypothermic CPB. CONCLUSIONS: SvO2 is not a good predictor of SjO2 during pediatric cardiac surgery with CPB, and low SjO2 can be undetected measuring SvO2 only.